Book Review: Wąsosz. Historia miasta i gminy [Wąsosz. History of City and Municipality] - Miłosz , Jan (Studia Historiae Oeconomicae, 2024)
The book Wąsosz. Historia Miasta i Gminy [Wąsosz: History of the City and Municipality], authored by Krzysztof Popiński (2022), a scholar at the Department of Philosophy and Economic History at Wrocław University of Economics, offers a comprehensive history of Wąsosz, a Lower Silesian town located at the intersection of Silesia [Śląsk] and Greater Poland [Wielkopolska]. This monograph serves as a gateway to understanding the region’s multifaceted past, uncovering layers of history that extend far beyond the memories of its current residents. By focusing on Wąsosz, the book provides a nuanced perspective on the complex historical developments of the Silesian region. It is a valuable resource for anyone interested in exploring Poland's regional history through the lens of a small, yet historically significant, town.